2012
DOI: 10.1186/1756-0500-5-536
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the CpxA sensor kinase and cognate CpxR response regulator from Yersinia pseudotuberculosis

Abstract: BackgroundThe CpxA sensor kinase-CpxR response regulator two-component regulatory system is a sentinel of bacterial envelope integrity. Integrating diverse signals, it can alter the expression of a wide array of components that serve to shield the envelope from damage and to promote bacterial survival. In bacterial pathogens such as Yersinia pseudotuberculosis, this also extends to pathogenesis. CpxR is thought to dimerize upon phosphorylation by the sensor kinase CpxA. This phosphorylation enables CpxR bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…A). However, when the same two‐hybrid system was previously used, it was shown that the Y. pseudotuberculosis CpxR regulator self‐interacts only when one or both of the interactors contained only the CpxR receiver domain (Thanikkal et al ., ). Examination of the interaction between a full‐length L. pneumophila CpxR and the CpxR receiver domain as well between two CpxR receiver domains resulted in strong interaction (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A). However, when the same two‐hybrid system was previously used, it was shown that the Y. pseudotuberculosis CpxR regulator self‐interacts only when one or both of the interactors contained only the CpxR receiver domain (Thanikkal et al ., ). Examination of the interaction between a full‐length L. pneumophila CpxR and the CpxR receiver domain as well between two CpxR receiver domains resulted in strong interaction (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…A). Interestingly, when the Y. pseudotuberculosis CpxR regulator was examined using the same two‐hybrid system, no self‐interaction was observed using an identical mutation (Thanikkal et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…WT: virulence of mutant bacteria was not statistically different from the parent; ND, not determined . g Determined from conventional yeast two-hybrid assay (YTH; Figure 5 ; Francis et al, 2000 ) and bacterial adenylate cyclase two hybrid (BACTH; electronic Supplementary Material, Figure S3 ; Thanikkal et al, 2012 ). WT: robust interaction between YopN and TyeA; Null: no detectable binding between YopN and TyeA; WT-like: a modest interaction between YopN and TyeA.…”
Section: Resultsmentioning
confidence: 99%
“…Aspartate 51 of CpxR is phosphorylated by CpxA, leading to active CpxR, which can then stimulate transcription. Changing the aspartate residue to glutamate, which mimics aspartyl-phosphate, can result in constitutive activation (37,38). The S. flexneri efp mutant producing CpxR D51E was tested for invasion and plaque formation to determine whether CpxA-independent activation of CpxR would suppress the virulence defect of the efp mutant.…”
Section: Resultsmentioning
confidence: 99%